High-strength self-leveling floor material and application thereof
High-strength self-leveling flooring materials are prepared by using a specific ratio of cement-based material compositions, which solves the segregation problem, improves the fluidity and compressive strength of the flooring, and meets the high requirements of modern industrial environments.
Patent Information
- Application Number
- CN202411540855.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
Existing self-leveling flooring materials are prone to segregation during construction, resulting in uneven floor surfaces that fail to meet high precision requirements. Furthermore, they lack durability in high-temperature, high-humidity, and organic acid/alkali corrosive environments, making them unsuitable for the high demands of modern industry.
A high-strength self-leveling flooring material is prepared by vacuum mixing a composition of cement, limestone powder, silica fume, bentonite, polyvinyl alcohol, redispersible latex powder, air-entraining agent, plasticizer, and stabilizer in a specific ratio, ensuring the material's fluidity and compressive strength.
A high-strength self-leveling flooring material with high fluidity, low dimensional change rate, and high compressive strength has been obtained, which is suitable for modern industrial environments and improves the durability and construction efficiency of the flooring.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building ground construction, and in particular relates to a high-strength self-leveling floor material and an application thereof. Background Art
[0002] In recent years, with the rapid development of the construction industry, the demand for building materials has continued to increase. As an important part of construction projects, the performance and application of floor materials have attracted widespread attention. Floor materials must not only meet the basic requirements of load-bearing and durability, but also have good construction performance, decorative properties, and chemical corrosion resistance. According to the needs of different application fields, the performance of floor materials in different environments also has different focuses. Especially in the industrial, commercial and residential fields, higher requirements are placed on the performance of the floor. Self-leveling floor materials have gradually become the mainstream choice of the market, and are favored for their convenient construction, high flatness and good durability. However, the self-leveling floor materials in the existing technology still have many shortcomings and challenges.
[0003] Although traditional cement-based self-leveling floor materials have good performance in construction convenience and durability, they often have segregation phenomenon, that is, during the construction process, the fine aggregate in the material is easy to sink due to density differences, resulting in uneven surface, insufficient strength and reduced durability of the final floor. Segregation not only affects the fluidity and molding effect of the material, but also causes the floor surface to be uneven, making it difficult to meet the requirements of modern buildings for high-precision floors.
[0004] On the other hand, modern industry has increasingly stringent requirements for floor materials, especially in high-end manufacturing fields such as new energy, electronics, medical, food, and chemical industry. These industries have put forward stringent requirements on the cleanliness of the production environment, chemical corrosion resistance, wear resistance, and compressive resistance of the floor. Existing floor materials, especially floor materials based on epoxy resin, although they have certain wear resistance and decorative effects, perform poorly in high temperature, high humidity, and organic acid and alkali corrosion environments, and lack durability, making it difficult to meet the high requirements of modern industrial production for material stability. In addition, the construction process of epoxy resin floor materials is complex, the process is cumbersome, and the construction efficiency is low, which is not conducive to large-scale rapid construction and commissioning.
[0005] Some existing improved technologies, such as water-based polyurethane mortar floor materials, have improved in terms of high temperature resistance, moisture resistance and chemical corrosion resistance, but they are still insufficient in terms of heavy-load compression resistance, wear resistance and surface decoration performance. Especially in the face of extremely harsh working environments, they are susceptible to scratches, wear and pollution, which affects their service life.
[0006] In summary, the existing self-leveling floor material technology, especially in how to solve the segregation phenomenon and adapt to the complex environment with high requirements of modern industry, still has many technical difficulties, which urgently need further research and improvement. Summary of the invention
[0007] The purpose of the present invention is to provide a high-strength self-leveling floor material and application thereof to solve technical problems.
[0008] A high-strength self-leveling floor material, comprising: Cement, 300 to 400 parts by weight; Limestone powder, 30 to 50 parts by weight; Silica fume, 5 to 10 parts by weight; Bentonite, 3 to 6 parts by weight; Polyvinyl alcohol, 0.1 to 0.5 parts by weight; Redispersible latex powder, 5 to 8 parts by weight; Air entraining agent, 0.1 to 0.3 parts by weight; Plasticizer, 0.5 to 2 parts by weight; Hydroxyethyl cellulose, 0.5 to 1 parts by weight; Stabilizer, 1 to 2 parts by weight.
[0009] In the high-strength self-leveling floor material of the present invention as described above, preferably, the air entraining agent is selected from one, two or three of sodium methane sulfonate, fatty acid salts and polyvinyl alcohol.
[0010] In the high-strength self-leveling floor material of the present invention as described above, preferably, the content of the air entraining agent is 0.24 parts by weight.
[0011] In the high-strength self-leveling floor material of the present invention as described above, preferably, the plasticizer is selected from one or both of diallyl phthalate and acetate; the content of the plasticizer is 0.8 to 1.5 parts by weight.
[0012] In the high-strength self-leveling floor material of the present invention as described above, preferably, the stabilizer is selected from one, two or three of sodium alginate, phosphate ester and magnesium aluminum silicate.
[0013] The present invention also provides another high-strength self-leveling floor material, which is composed of the following components in the following weight ratio: 300 to 400 parts by weight of cement; 30 to 50 parts by weight of limestone powder; 5 to 10 parts by weight of silica fume; 3 to 6 parts by weight of bentonite; 0.1 to 0.5 parts by weight of polyvinyl alcohol; 5 to 8 parts by weight of redispersible latex powder; 0.24 parts by weight of air entraining agent; 0.5 to 2 parts by weight of plasticizer; 0.5 to 1 parts by weight of hydroxyethyl cellulose; and 1 to 2 parts by weight of stabilizer.
[0014] In the high-strength self-leveling floor material of the present invention as described above, preferably, the air entraining agent is selected from one, two or three of sodium methane sulfonate, fatty acid salts and polyvinyl alcohol.
[0015] In the high-strength self-leveling floor material of the present invention as described above, preferably, the plasticizer is selected from one or both of diallyl phthalate and acetate; the content of the plasticizer is 0.8 to 1.5 parts by weight.
[0016] In the high-strength self-leveling floor material of the present invention as described above, preferably, the stabilizer is selected from one, two or three of sodium alginate, phosphate ester and magnesium aluminum silicate.
[0017] The present invention also provides the use of a high-strength self-leveling floor material in self-leveling floor construction, wherein the high-strength self-leveling floor material is the high-strength self-leveling floor material as described in any one of the above items.
[0018] The beneficial effects of the present invention are: by utilizing the selection of components of the composition of the present invention, the weight ratio between the components and the synergistic relationship between the components, a high-strength self-leveling floor material with high fluidity, small dimensional change rate and high compressive strength can be obtained, and the self-leveling floor can be constructed. DETAILED DESCRIPTION
[0019] The embodiments described herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention, are illustrative and exemplary, and should not be construed as limiting the embodiments of the present invention and the scope of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the claims and the contents disclosed in the specification of this application, including technical solutions that adopt any obvious replacement and modification of the embodiments described herein.
[0020] In the following examples, the specific specifications or sources of the materials used are as follows: Cement, the cement used in the present invention can be selected from cement with the label number 425 or 525; in the following embodiments, ordinary silicate cement PO42.5R produced by Yanxin Holding Group Co., Ltd. is selected. Limestone powder, produced by Hebei Leijiang New Materials Technology Co., Ltd., 1250 mesh. Silica fume, Shijiazhuang Baijiang Mineral Products Co., Ltd., 1250 mesh. Bentonite, Shanghai Zhenlishi Network Technology Co., Ltd., 1.8g / cm³, effective ingredient content greater than 99%. Polyvinyl alcohol, Inner Mongolia Shuangxin Environmental Protection Materials Co., Ltd., PVA088-20 (1788), powder 80 mesh. Hydroxyethyl cellulose, the hydroxyethyl cellulose (HEC) used in the present invention is Renqiu Pengyu Chemical Co., Ltd., density 0.75g / cm³ (25°C). Redispersible latex powder, purchased from Hebei Chaoyan New Materials Technology Co., Ltd., average particle size 80μm, 50% aqueous solution viscosity ≥10.0pas.
[0021] Air entraining agent, sodium methane sulfonate was purchased from Jinan Lanjue Trading Co., Ltd., 99wt% content. Fatty acid salt is sodium stearate, purchased from Henan Yilu Chemical Technology Co., Ltd., 99wt% content. Polyvinyl alcohol was purchased from Anhui Longyang Environmental Protection Technology Co., Ltd., viscosity 68.0-78.0, 99.9wt% content Plasticizer, diallyl phthalate was purchased from Shandong Deyitai New Materials Co., Ltd., with an effective ingredient content of 99 wt%. Propylene glycol methyl ether acetate was purchased from Chengdu Xinghaitian Chemical Co., Ltd., with a high-grade pure G.
[0022] The stabilizer is selected from one, two or three of sodium alginate, phosphate ester and magnesium aluminum silicate.
[0023] Sodium alginate, purchased from Shaanxi Shengqi Biotechnology Co., Ltd., with an effective ingredient content of 99 wt%. Sodium polyacrylic acid salt, purchased from Jiangsu Leien Environmental Protection Technology Co., Ltd., with an effective ingredient content of 99 wt%. Magnesium aluminum silicate, purchased from Zhengzhou Maliang Chemical Co., Ltd., 325 mesh.
[0024] The preparation method of the high-strength self-leveling floor material of the present invention is as follows: Step 1, preparing group A materials: adding cement, limestone powder, silica fume and bentonite into a vacuum high-speed stirring disperser according to the formula ratio, stirring and mixing at room temperature for at least 30 minutes, then adding air entraining agent and plasticizer, stirring and mixing at room temperature for at least 30 minutes, and then sealing and packaging to obtain group A materials; Step 2, prepare group B materials: stir polyvinyl alcohol, redispersible latex powder and hydroxyethyl cellulose to react for 1 to 1.5 hours; under stirring conditions, add stabilizer according to the formula ratio and mix for 0.5 hours, and seal and package to obtain component B; when using, mechanically mix component A and component B to obtain high-strength self-leveling floor material. During construction, the weight ratio of high-strength self-leveling floor material to water is 1: (2 to 3.5).
[0025] Example 1 The high-strength self-leveling floor material of this embodiment includes: 300 parts by weight of cement; 50 parts by weight of limestone powder; 5 parts by weight of silica fume; 6 parts by weight of bentonite; 0.1 parts by weight of polyvinyl alcohol; 8 parts by weight of redispersible latex powder; 0.1 parts by weight of sodium methane sulfonate; 2 parts by weight of diallyl phthalate; 0.5 parts by weight of hydroxyethyl cellulose; and 2 parts by weight of sodium alginate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0026] Example 2 The high-strength self-leveling floor material of this embodiment includes: 400 parts by weight of cement; 30 parts by weight of limestone powder; 10 parts by weight of silica fume; 3 parts by weight of bentonite; 0.5 parts by weight of polyvinyl alcohol; 5 parts by weight of redispersible latex powder; 0.3 parts by weight of fatty acid salt; 0.5 parts by weight of acetate; 1 part by weight of hydroxyethyl cellulose; and 1 part by weight of phosphate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0027] Example 3 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of polyvinyl alcohol; 0.8 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of magnesium aluminum silicate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0028] Example 4 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of polyvinyl alcohol; 1.5 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of magnesium aluminum silicate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0029] Example 5 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of sodium methane sulfonate; 1.5 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of magnesium aluminum silicate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0030] Example 6 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of fatty acid salt; 1.5 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of magnesium aluminum silicate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0031] Example 7 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of polyvinyl alcohol; 1.5 parts by weight of acetate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of magnesium aluminum silicate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0032] Example 8 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.22 parts by weight of polyvinyl alcohol; 1.5 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of magnesium aluminum silicate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0033] Example 9 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.26 parts by weight of polyvinyl alcohol; 1.5 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of magnesium aluminum silicate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0034] Example 10 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of polyvinyl alcohol; 1.5 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of sodium alginate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0035] Embodiment 11 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of polyvinyl alcohol; 1.5 parts by weight of diallyl phthalate; 0.8 parts by weight of hydroxyethyl cellulose; and 1.4 parts by weight of phosphate. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method.
[0036] Example 12 The high-strength self-leveling floor material of this embodiment includes: 360 parts by weight of cement; 38 parts by weight of limestone powder; 7 parts by weight of silica fume; 5 parts by weight of bentonite; 0.3 parts by weight of polyvinyl alcohol; 6.4 parts by weight of redispersible latex powder; 0.24 parts by weight of polyvinyl alcohol; 1.5 parts by weight of diallyl phthalate; and 0.8 parts by weight of hydroxyethyl cellulose. The high-strength self-leveling floor material is prepared according to the above-mentioned preparation method (without adding a stabilizer).
[0037] Performance Testing The specific provisions of the conditions, equipment, specimen preparation, test result calculation, etc. involved in the following performance test process refer to cement-based self-leveling mortar for floor (JC / T985-2017).
[0038] 1. Initial fluidity: start timing after the specimen is prepared. After 4 minutes, measure the diameters in two perpendicular directions and take the arithmetic mean as the measured value.
[0039] 2. 20-minute fluidity: let the same batch of samples stand in the stirrer for 20 minutes after stirring, then stir at a low speed for 15 seconds, measure the diameters in two vertical directions, and take the arithmetic mean as the measured value.
[0040] 3. Tensile bond strength. Test steps: After demoulding, the specimen is placed under standard test conditions until the age of 27 days. The surface slurry is polished off with sandpaper, and then the tensile joint is bonded to the forming surface of the specimen with a suitable high-strength adhesive. After continuing to place under standard test conditions for 24 hours, load is applied using a tensile testing machine with a tensile speed of (5±1) mm / min.
[0041] 4. Dimensional change rate, specimen preparation, apply a thin layer of demoulding oil on the inner surface of the shrinkage mold, fix the shrinkage head in the holes on both ends of the test mold, and make the shrinkage head protrude (8±1)mm from the end face of the specimen. Prepare the specimen according to 7.1, pour the mixed specimen into the shrinkage test mold without vibration, use a metal scraper to remove excess mortar, make the mortar completely fill the mold and make the surface flat, three specimens are a group. Test steps, demould after placing under standard test conditions for 24 hours, and number and mark the measurement direction. Before measurement, use the standard rod to adjust the origin of the dial indicator of the shrinkage instrument. Within 30 minutes after demoulding, measure the length of the specimen in the marked measurement direction, which is the initial length of the specimen (L0). After measuring the initial length, the specimen should be placed under standard test conditions for curing. After 28 days, measure the length of the specimen in the marked measurement direction, which is the length after natural drying (L1).
[0042] 5. 28d compressive strength and 28d flexural strength, test procedures: demould the specimen after 24h, continue to cure under standard test conditions until 28d age, measure the 24h compressive strength and flexural strength according to GB / T17671, and measure its flexural and compressive strength.
[0043] The corresponding performance test results of Examples 1 to 12 are shown in Table 1.
[0044] Table 1 Number / Performance Initial fluidity (mm) 20min fluidity (mm) Tensile bond strength / Mpa Dimension change rate / % 28d compressive strength / Mpa 28d flexural strength / Mpa Example 1 172 134 2.6 -0.04 25.2 6.5 Example 2 183 142 2.4 -0.03 36.0 7.2 Example 3 176 135 2.2 -0.05 26.3 7.0 Example 4 185 163 2.8 -0.02 36.0 7.3 Example 5 170 130 2.5 -0.04 18.4 5.0 Example 6 179 140 2.3 -0.04 18.8 5.7 Example 7 168 133 1.9 -0.03 19.3 5.1 Example 8 167 143 2.7 -0.05 24.5 7.0 Example 9 177 138 2.2 -0.03 26.2 6.9 Example 10 180 132 2.0 -0.03 20.0 5.2 Embodiment 11 178 145 2.3 -0.04 20.4 5.8 Example 12 176 137 2.6 -0.16 20.8 7.5 The data in Table 1 above illustrate that by utilizing the selection of components of the composition of the present invention, the weight ratio between the components and the synergistic relationship between the components, a high-strength self-leveling floor material with high fluidity, low dimensional change rate and high compressive strength can be obtained, which can be used for self-leveling floor construction.
[0045] The technical features disclosed above are not limited to the disclosed combinations with other features. Those skilled in the art may also make other combinations between the technical features according to the purpose of the invention to achieve the purpose of the invention.
Claims
1. A high-strength self-leveling floor material, characterized in that: include: Cement, 300 to 400 parts by weight; Limestone powder, 30 to 50 parts by weight; Silica fume, 5 to 10 parts by weight; Bentonite, 3 to 6 parts by weight; Polyvinyl alcohol, 0.1 to 0.5 parts by weight; Redispersible latex powder, 5 to 8 parts by weight; Air entraining agent, 0.1 to 0.3 parts by weight; Plasticizer, 0.5 to 2 parts by weight; Hydroxyethyl cellulose, 0.5 to 1 parts by weight; Stabilizer, 1 to 2 parts by weight.
2. The high-strength self-leveling floor material according to claim 1, characterized in that: The air entraining agent is selected from one, two or three of sodium methane sulfonate, fatty acid salt and polyvinyl alcohol.
3. The high-strength self-leveling floor material according to claim 1, characterized in that: The content of the air entraining agent is 0.24 parts by weight.
4. The high-strength self-leveling floor material according to claim 1, characterized in that: The plasticizer is selected from one or both of diallyl phthalate and acetate; the content of the plasticizer is 0.8 to 1.5 parts by weight.
5. The high-strength self-leveling floor material according to claim 1, characterized in that: The stabilizer is selected from one, two or three of sodium alginate, phosphate ester and magnesium aluminum silicate.
6. A high-strength self-leveling floor material, characterized in that: The invention is composed of the following components in the following weight proportions: 300 to 400 parts by weight of cement; 30 to 50 parts by weight of limestone powder; 5 to 10 parts by weight of silica fume; 3 to 6 parts by weight of bentonite; 0.1 to 0.5 parts by weight of polyvinyl alcohol; 5 to 8 parts by weight of redispersible latex powder; 0.24 parts by weight of air entraining agent; 0.5 to 2 parts by weight of plasticizer; 0.5 to 1 parts by weight of hydroxyethyl cellulose; and 1 to 2 parts by weight of stabilizer.
7. The high-strength self-leveling floor material according to claim 7, characterized in that: The air entraining agent is selected from one, two or three of sodium methane sulfonate, fatty acid salt and polyvinyl alcohol.
8. The high-strength self-leveling floor material according to claim 7, characterized in that: The plasticizer is selected from one or both of diallyl phthalate and acetate; the content of the plasticizer is 0.8 to 1.5 parts by weight.
9. The high-strength self-leveling floor material according to claim 7, characterized in that: The stabilizer is selected from one, two or three of sodium alginate, phosphate ester and magnesium aluminum silicate.
10. Application of high-strength self-leveling floor material in self-leveling floor construction, wherein the high-strength self-leveling floor material is the high-strength self-leveling floor material described in any one of claims 1-9.
Citation Information
Cited By
Composite curing agent as well as preparation method and application thereof
CN122127121A
Composite curing agent, preparation method and application thereof
CN122127121B